Corporate Governance, Capital Reserve, Non-Performing Loan, and Bank Risk Taking - Lestari, Diyan (International Journal of Economics and Financial Issues, 2018)
This study aim to analyze the effect of corporate governance, bank capital reserve, and NPL on bank risk taking which listed in Indonesia Stock Exchange from 2009 to 2016. The corporate governance represent management decision making and bank management policy related to risk and other banking issue. While capital reserve and non-performing loan indicate bank financial performace. Capital reserve is important indicator for bank compare to its risky activities, and non-performing loan will give bank information about bank effectivity in lending behavior. The result of this study show that ownership concentration, the big four audit committee, and non-performing loan has negative effect on bank risk taking behavior. While capital reserve is not statistically significant on bank risk taking. Keywords: corporate governance, capital reserve, non-performing loan, bank risk taking JEL Classifications: G3, G32